Hydrothermal synthesis of Polypyrrole/MoS2 intercalation composites for supercapacitor electrodes. Issue 13 (September 2017) - Lian, Meng; Wu, Xinming; Wang, Qiguan; Zhang, Wenzhi; Wang, Yan
Abstract: As a pseudocapacitive electrode materials for supercapacitor, Polypyrrole (PPy) exhibit excellent theoretical specific capacitance. However, it suffers from a poor cycling stability due to structural instability during charge-discharge process. In this work, a novel and facile hydrothermal method has been developed for the intercalation composites of PPy/MoS2 with multilayer three-dimensional structure. The report result shows that the as-prepared electrode possess a outstanding electrochemical properties with significantly specific capacitance of 895.6 F g −1 at current density of 1 A g −1, higher energy density (3.774 Wh kg −1 ) at power density of 252.8 kW kg −1, furthermore, it also achieve remarkable cycling stability (~98% capacitance retention after 10, 000 cycles) which is attributed to the synergistic effect of PPy and MoS2 . This synthetic strategy integrates performance enables the multilayer PPy/MoS2 composites to be a promising electrode for energy storage applications.